2017
DOI: 10.1136/archdischild-2016-312533
|View full text |Cite
|
Sign up to set email alerts
|

Severe retinopathy of prematurity predicts delayed white matter maturation and poorer neurodevelopment

Abstract: Severe ROP is associated with maturational delay in the optic radiations, PLIC, external capsule and posterior white matter, housing the primary visual and motor pathways, and is associated with poorer cognitive and motor outcomes at 18 months' CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 32 publications
(9 reference statements)
9
63
0
Order By: Relevance
“…We were able to show that preterm-born children with severe ROP displayed a significantly lower development quotient and lower fine motor scores at 15 and 24 months' CA, which is in agreement with other publications (28,29). Smaller brain volumes and impaired cortical development have been associated with neurodevelopmental deficits that persist through childhood and adolescence (30).…”
Section: Discussionsupporting
confidence: 91%
“…We were able to show that preterm-born children with severe ROP displayed a significantly lower development quotient and lower fine motor scores at 15 and 24 months' CA, which is in agreement with other publications (28,29). Smaller brain volumes and impaired cortical development have been associated with neurodevelopmental deficits that persist through childhood and adolescence (30).…”
Section: Discussionsupporting
confidence: 91%
“…As previous studies have reported the association between white matter maturation delay and cognitive outcomes in children born preterm, 12,29 our findings may provide functional implications in preterm infants with ROP. Clinical outcomes of ROP have improved greatly since the introduction of laser and anti-vascular endothelial growth factor therapy for severe retinopathy.…”
Section: Discussionsupporting
confidence: 69%
“…In line with our outcome, several publications have emphasised the risk of late death or major disabilities in childhood born preterm with severe ROP or BPD. Farooqi et al.…”
Section: Discussionsupporting
confidence: 75%